Contextual cue utilization in visual anticipation in tennis: On the role of an opponent`s on-court position and skill - Huesmann, K.; Loffing, F. (German Journal of Exercise and Sport Research, 2019)
In batting and racket sports, players rely on kinematic and contextual cues to anticipate an opponent`s action outcome. In tennis, an opponent`s on-court position has been found to be a contextual cue signaling stroke direction. Additionally, given the varying technical-tactical repertoire associated with an opponent`s skill, the latter may further influence prediction behavior. Here, we sought to replicate position dependency in visual anticipation and to test the hypothesized interaction between an opponent`s on-court position and skill upon stroke direction anticipation in tennis. To this end, skilled tennis players predicted shot direction of point-light animated forehand groundstrokes that were executed at different on-court positions and occluded at three different time points. In block 1, no skill information was given, whereas in blocks 2 and 3 participants were told to either face opponents from the Bundesliga or Kreisliga. In line with former evidence, shot outcome predictions varied as a function of an opponent`s on-court position. Also, participants` reliance on position information was strongest when little kinematic information was available. However, knowledge of an opponent`s purported skill was not found to reliably affect prediction behavior. By contrast, post-experiment questionnaire data suggest that players explicitly assign different shot direction probabilities depending on an opponent`s skill and position. Collectively, our research supports especially the role of on-court position for tennis stroke outcome anticipation. The conflicting findings on the potential role of knowledge of an opponent`s skill call for further empirical verification. In (Rück-)Schlagsportarten verlassen Athleten sich auf kinematische und kontextbezogene Informationen zur Antizipation des gegnerischen Handlungsausgangs. Im Tennis ist die gegnerische Position auf dem Platz ein Kontextmerkmal, welches zur Vorhersage der Schlagrichtung genutzt wird. Aufgrund variierender technisch-taktischer Fertigkeiten in Abhängigkeit vom Leistungsniveau eines Gegners könnte Letzteres ebenfalls das Antizipationsverhalten beeinflussen. Ziel der vorliegenden Studie war es, Befunde zur positionsabhängigen visuellen Antizipation zu replizieren und die vermutete Interaktion zwischen gegnerischer Position und Leistungsniveau im Hinblick auf die Antizipation der Schlagrichtung im Tennis zu prüfen. Erfahrene Tennisspieler hatten die Aufgabe, die Richtung lichtpunktanimierter Vorhandgrundlinienschläge vorherzusagen, die von unterschiedlichen Positionen auf dem Platz ausgeführt wurden und zu drei verschiedenen Zeitpunkten abbrachen. In Block 1 wurden keine Informationen über das gegnerische Leistungsniveau gegeben. In den Blöcken 2 und 3 hingegen wurde den Probanden mitgeteilt, dass sie entweder gegen einen Bundesliga- oder einen Kreisligaspieler spielten. Im Einklang mit früheren Studien variierten die Schlagrichtungsvorhersagen in Abhängigkeit von der gegnerischen Platzposition, insbesondere wenn wenig kinematische Informationen verfügbar waren. Ein Einfluss des Wissens über das vermeintliche gegnerische Leistungsniveau auf das Antizipationsverhalten konnte hingegen nicht zuverlässig nachgewiesen werden. Demgegenüber legen die Ergebnisse einer postexperimentellen Befragung nahe, dass Tennisspieler abhängig vom Leistungsniveau und der Platzposition des Gegners explizit unterschiedliche Schlagrichtungswahrscheinlichkeiten erwarten. Zusammenfassend unterstreichen die Ergebnisse insbesondere die Relevanz der gegnerischen Position für die Antizipation der Schlagrichtung im Tennis. Die gegensätzlichen Befunde zum potenziellen Einfluss des Wissens über das gegnerische Leistungsniveau verlangen nach einer weiteren empirischen Überprüfung.